Arabic Language Education for Non-Native Speaker: Integrating Local Culture - Khairanis, Retisfa; Aldi, Muhammad (Yayasan Nurul Musthafa, 2025)
Arabic language education for non-native speaker is increasingly important along with globalization and the need to understand Arabic culture. However, challenges arise when teaching materials do not pay attention to the local cultural context which can hinder the learning process. This research aims to explore the integration of local culture in Arabic language education for non-native speaker so that learning becomes more contextual and relevant. The research method used was a qualitative descriptive method through observation and interviews with teachers and students at MTsN 2 Padang, West Sumatra. The results showed that the integration of local culture can improve Arabic language understanding, facilitate adaptation, and make the learning process more interesting and effective. In conclusion, the incorporation of local cultural elements in the Arabic language education curriculum not only enriches the learning experience, but also accelerates language acquisition and encourages students to appreciate cultural diversity. [Pendidikan bahasa Arab bagi penutur non-native semakin penting seiring dengan globalisasi dan kebutuhan untuk memahami budaya Arab. Namun, tantangan muncul ketika materi ajar tidak memperhatikan konteks budaya lokal yang dapat menghambat proses pembelajaran. Penelitian ini bertujuan untuk mengeksplorasi integrasi budaya lokal dalam pendidikan bahasa Arab untuk non-native speaker sehingga pembelajaran menjadi lebih kontekstual dan relevan. Metode penelitian yang digunakan adalah metode kualitatif dengan jenis deskriptif melalui observasi dan wawancara terhadap pengajar dan siswa di MTsN 2 Kota Padang, Sumatera Barat. Hasil penelitian menunjukkan bahwa integrasi budaya lokal dapat meningkatkan pemahaman bahasa Arab, mempermudah adaptasi, dan membuat proses pembelajaran lebih menarik dan efektif. Kesimpulannya, penggabungan unsur budaya lokal dalam kurikulum pendidikan bahasa Arab tidak hanya memperkaya pengalaman belajar, tetapi juga mempercepat penguasaan bahasa serta mendorong siswa untuk lebih menghargai keragaman budaya.]